2020
DOI: 10.1111/jir.12760
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and cultural needs of children with intellectual disability and their families among the Syrian refugee population in Turkey

Abstract: BackgroundTurkey is the country hosting the largest number of refugees from Syria, with currently 3 571 175 million persons. The general health needs of the refugees are being addressed; however, people with intellectual disabilities (IDs), particularly children, are relatively missed. The aim of this study was to identify medical, psychological and social needs of children with ID and their families, among the Syrian refugee population in Turkey, and to define psychosocial and cultural needs for planning of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Furthermore, they sated that they usually spent the day helping their mothers, they could do chores, but they were not recognized by anyone. Similarly, in studies where the needs of refugees with special needs were emphasized, the need for special education, lack of access to childcare and employment resources were reported (Acartürk et al, 2021;Dew et al, 2020;Öner et al, 2020). Thus, although the present study findings were consistent with the literature, they highlighted the requirements in special education, care, and employment.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Furthermore, they sated that they usually spent the day helping their mothers, they could do chores, but they were not recognized by anyone. Similarly, in studies where the needs of refugees with special needs were emphasized, the need for special education, lack of access to childcare and employment resources were reported (Acartürk et al, 2021;Dew et al, 2020;Öner et al, 2020). Thus, although the present study findings were consistent with the literature, they highlighted the requirements in special education, care, and employment.…”
Section: Discussionsupporting
confidence: 86%
“…Certain mothers stated that they had free access to healthcare, others stated that they had to pay for healthcare. Previous studies reported that the most requirement of the refugees were childcare, healthcare, employment, and special education (Acartürk et al, 2021;Karadağ & Çalışgan, 2021;Öner et al, 2020). Also, a study reported that refugee parents were satisfied with the available education in general, but they demanded Turkish language education for their children (Bal et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Worldwide, the group of migrant children with ID is estimated at 5 million (Bešic & Hochgatterer, 2020). Due to linguistic and cultural differences, lack of knowledge about the healthcare system, and their socio-economic circumstances (Piérart et al, 2020), migrant parents of children with ID have been found to have higher needs for information and financial support (Oner et al, 2020). One of the first studies exploring experiences of migrant parents of children with ID showed that migrant parents described accessing healthcare as challenging, since they felt that their concerns about their child with ID had not been taken seriously and that they did not receive the help they needed (Arfa et al, 2020).…”
mentioning
confidence: 99%